Parametrische Ösophagusszintigramme von Passageuntersuchungen in Mehrfachschlucktechnik: Vergleich einer neuen Methode mit einem StandardÖsophagustransittest - Tatsch, K.; Schröttle, W.; Kirsch, C.-M. (Nuklearmedizin - NuclearMedicine, 1990)
Established single-swallow techniques for the assessment of oesophageal motility disorders encompass a high potential of falsely positive/negative findings caused by the considerable variability between single swallows. In this study, therefore, a new form of parametric oesophageal scintigraphy (POeS) is introduced which allows simultaneous assessment of 15-20 consecutive swallows. To assess the value of this combined qualitative/semiquantitative method 166 patients with various oesophageal motility disorders were tested in an intraindividual comparison with a standard oesophageal transit test (OeTT). In contrast to OeTT, POeS yields specific image patterns which permit a differentiation between various forms of peristaltic disorder. By the use of POeS the bolus behaviour during its oesophageal passage is well characterized, the main location of the functional disorder can be identified and a correct classification of the severity can be achieved as well. In contrast to OeTT, diagnosis in POeS is based on a series of consecutive swallows. Misinterpretation due to possible variations between single swallows is often observed in OeTT, providing up to 30% false-positive and 52% false-negative findings which are almost eliminated using POeS.